On the Edge. Relics of LBK Settlement at the Site of Kruszyn 3, Commune Włocławek (Household A) - Rzepecki, Seweryn; Domańska, Lucyna (Analecta Archaeologica Ressoviensia, 2024)
The aim of the article is to present the LBK sources recorded in the northern part of the site of Kruszyn 3, commune Włocławek. A special feature of the site is its location on the edge of the Kuyavia Lake District and the Płock Basin. The former was intensively settled in the Early Neolithic, while the latter was anecumene. The complex of finds described in the article consists of the remains of a house, outbuildings, a relatively numerous pottery assemblage and less numerous flints, stone tools, and animal bone remains. The entire site dates to phase II (Music-Note Phase) of the LBK in Kuyavia.